Pendidikan Keluarga Menurut Al-Qur’an Surat At-Tahrim Ayat 6 - Rohinah (AN NUR: Jurnal Studi Islam, 2015)
The family as the smallest public entities in the life of the nation actually has a role and a function that can not be ignored.The family as the smallest public entities in the life of the nation actually has a role and a function that can not be ignored. Of family life that humans live and develop physical and spiritual. Human life in the later period is determined from family life gained. Therefore, in education, family education is the main foundation of the nation as a moral forming. Because the real moral education in Islam should start early. And moral education is also a principle to be considered for fostering a strong and harmonious family. Therefore, the Qur’an as the main foundation of Islamic education gives a hint that this is the moral education that guarantees the establishment of Islamic family strong, colorful love and ensure the establishment of a healthy human body, mind, and soul.